Characterization of global research trends and prospects on celastrol, a principal bioactive ingredient of Tripterygium wilfordii Hook F: bibliometric analysis - Ye, Huizi; Wang, Yufang; Zhang, Xue; Yang, Lin; Cai, Banglan; Zhang, Denghai; Peng, Bin (Pharmaceutical biology, 2025)
Celastrol, acknowledged as a prominent exemplar of the potential for transforming traditional medicinal compounds into contemporary pharmaceuticals, has garnered considerable attention owing to its extensive pharmacological activities. The increasing volume of publications concerning celastrol highlights its importance in current scientific inquiry. Despite the growing interest in this compound, a bibliometric analysis focused on this subject remains to be undertaken. Our study explored a bibliometric approach to identify and characterize global research trends and frontiers related to celastrol, including mapping research outputs, influential contributors, and thematic areas, as well as highlighting gaps and opportunities for future investigations. In this study, we utilized the Web of Science Core Collection (WoSCC) to source and review articles related to celastrol published from 1997 to 2023. The bibliometric analysis was conducted using the R package 'Bibliometrix,' supplemented by visualization tools including CiteSpace, VOSviewer, and GraphPad Prism 10. Celastrol related research papers have exhibited an upward trend annually and can be categorized into three distinct phases, each highlighting different areas of focus. China, the United States, and South Korea rank as the top three nations for publication volume, with varied research interests across these countries. Several prolific research teams have emerged, each with distinct areas of interest. Examining the primary research domains of celastrol (anti-inflammatory, anticancer, and toxicity) reveals a notable intersection between the first two domains. The scope and depth of celastrol research have been steadily expanding, with regional and team-specific variations. Key research areas include anti-inflammatory, anticancer, and toxicity studies. Future research is expected to focus on enhancing the effectiveness and reducing the toxicity of celastrol. Meanwhile, given the multi-target characteristics of celastrol's effects, integrating methods such as network biology and molecular simulation will provide a novel perspective for celastrol research.